Development of Student Worksheets in the Context of Wetlands in the Sub-Material of Water Pollution in Grade VII Middle School - Aprilia, Aprilia; Mutika Sari, Mella; Febriyani Putri, Rizky (Journal of World Science, 2023)
The teacher can use various learning methods to make it easier for students to process learning outcomes, and what has been planned can be achieved as well and as easily as possible by students. Therefore, the researcher wants to develop LKPD with Wetland Context on water pollution sub-materials. The wetlands presented in this study are rivers that will be directly observed for pollution that occurs in the river. This research is research and development using a 4D model (define, design, develop and disseminate). This research was conducted at SMP Negeri 15 Banjarmasin. The aims of the researchers in carrying out this development were 1) to validate the LKPD in the wetland context, 2) to determine the practicality of the LKPD in the wetland context, and 3) to determine the effectiveness of the LKPD in the wetland context. The research instruments include learning achievement tests, response questionnaires, and validation. LKPD obtains a validity value of 3.49 with valid criteria. Practicality gets a score of 82.00% with very practical criteria. Effectiveness with a gain calculation of 0.86 with high criteria. This LKPD is suitable for use in learning activities.